Exploring the development of a household cholera-focused health literacy scale in James Town, Accra - Raymond A. Tutu; Sangeeta Gupta; Sathyanarayana Elavarthi; Janice D. Busingye; John K. Boateng (Elsevier, 2019)
Background: Foodborne diseases are significant reasons for in-patient and out-patient morbidity in Ghana. Of the foodborne illnesses reported in the country, cholera incidence and outbreaks have resulted in food-related mortality since the disease was first reported in the 1970s. Cholera is now endemic in the country. This study attempts to develop and pilot a tool to measure household health literacy among the urban poor in James Town, a cholera endemic neighborhood. Methods: A survey questionnaire was developed based on four of the World Health Organization's (WHO) recommendations on issues for measurement of health literacy in low- and middle-income countries. The instrument was administered to 401 households in the community. We undertook reliability and validity analyses. T-test, Kruskal Wallis test, and Mann-Whitney test were used to examine the association between the health literacy scores of the scale and subscales and the demographic characteristics of households. Results: The reliability analyses showed that the instrument was internally consistent (Cronbach alpha = 0.762). All the subscales were reliable except the beliefs about health and healthcare subscale. Based on content and construct validity analyses, 13 items were used for further examination of health literacy. We found that majority of households know about the information, education, and communication materials and 52% of households indicated that these materials remind them about the dangers of cholera. About 39% of the households decide together as a unit on steps to avoid getting cholera during an outbreak. Overall health literacy scores and the subscales were significantly associated with sex, age, marital status, and educational level of household head. Specifically, females, being married, increasing age and higher household income had a significant association with higher health literacy scores. Conclusion: Household units in James Town impacts individual health literacy through: family discussions; access to information, education, and communication materials on cholera; and intentional efforts made to get information on cholera risk factors. Keywords: Cholera, Health literacy, Household health, Foodborne diseases, Infections, Ghana